The Effectiveness of Psychoeducational Group of Goal-Setting Training to Improve Self-Efficacy and Learning Motivation - Mawarni, Ai; Puji Sugiharto, Dwi Yuwono; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2022)
Self-efficacy and learning motivation are important for students because those affect the learning process, cognitive actions and increase effort through the student's ability to achieve academic goals. This study aimed to determine the effectiveness of the psychoeducational group of goal-setting training to improve self-efficacy and learning motivation of students at Mekar Arum Junior Hight Shool, Bandung Regency. This study used an experimental method with a randomized pretest-posttest control group design by involving 14 students with low to moderate self-efficacy and learning motivation levels as study subjects. The results of this study showed that the psychoeducational group of goal-setting training was effective in improving students' self-confidence in doing assignments, enthusiasm for learning and academic achievements at school. The results of the Wilcoxon Signed Rank Test and Mann-Whitney Test showed that the intervention of the goal-setting training psychoeducational group was effective in improving the self-efficacy and learning motivation of students at Mekar Arum Junior High School, Bandung Regency. The results and findings of the study, including implications and limitations are further discussed in the discussion section.